PEMBUATAN PERMEN HERBAL PADA TERNAK KAMBING DI DESA BUKIT SAMANG - Uli Fahrodi, Deka; Marsudi, Marsudi; Sukma Indah, Andi; Saidah Said, Nur; Dunialam Khaliq, Taufik; Putra Ermanda, Adli (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Bukit Samang, is one of the villages in Sendana District, Majene Regency, West Sulawesi. The livestock sector in this village is very developed, especially goat farming. Based on the results of observations in the field, the problem faced by the local community is the lack of veterinary medical personnel in the field, so goat health problems are not quickly resolved, causing farmers to experience losses. There is a lot of potential for plants that can be processed into traditional medicines to treat or prevent disease. The initial stage in mapping partner problems is to carry out a Focus Group Discussion (FGD), which aims to discover the issues Bukit Harapan Farmer Group partners face in Bukit Samang Village. The following are the problems partners face: First, Animal Health Problems. Sudden deaths often occur in goats due to late handling and treatment of sick livestock. Second: HR problems; Farmers' knowledge of plants that have potential as alternative/traditional medicines is still low. The solution offered is education on introducing diseases in goats and plants with potential as conventional medicines and training in making herbal medicines. It also produces new entrepreneurs who can create herbal medicine for livestock labeled "Batra Candy." Methods for implementing activities are initial survey preparation, determining partner targets, and implementing activity programs, namely participatory counseling, training, guidance, and mentoring. The training method is carried out with training in making herbal medicines; the final stage is monitoring and evaluation. From the analysis of questionnaires given to partners before and after service activities, there was an increase in the percentage of partners' knowledge regarding livestock health from 36% to 82%, breeders' knowledge regarding plants that have potential as alternative/traditional medicines also increased in percentage, namely before partner service activities. Did not know this potential (0%) then the rate increased to 92%. In general, implementing this activity informs livestock group members that several plants can be processed into livestock herbal candy, which has healing properties and prevents disease in livestock, to increase livestock production performance and breeder income.